Effect of the Injection Design on Drug Targeting in Molecular Communication - Wille, Luiz; Xiao, Keyu; Kirchner, Jens (NanoCom 2025 - Proceedings of the 12th ACM International Conference on Nanoscale Computing and Communication, 2025)
For testbed experiments in molecular communication, the injection method can significantly impact the results of the received signals. In this work, the impact of the injection flow rate on the uniform distribution of particles was studied by numerical simulation of a syringe injection in the direction of background flow for three different flow rates in 3D. A low injection rate seems to negatively impact the overall propagation of the particle bolus.
CRIS-Team Scopus Importer:2025-12-05
Keywords: drug targeting; injection; molecular communication